Increasing Trends or Sociodemographic Changes? Decomposition Analyses of Maternal Complication in Indonesia - Widyaningsih, V; ., Khotijah (KnE Life Sciences, 2019)
Many Indonesian women experienced self-reported complications during pregnancy and delivery. These complications include prolonged labor, bleeding, infection, and other complications. This study aimed to examine the underlying determinants that influenced the increasing prevalence of maternal complication in Indonesia. Data from the two most recent Indonesian Demographic and Health Surveys (IDHS) were analyzed. We quantified the contribution of socio-demographic factors in the increase of maternal complications, using Oaxaca-Blinder regression-based decomposition analyses with STATA ‘mvdcmp’ procedure. Between IDHS 2007 and IDHS 2012, there was a significant increase in maternal complication prevalence from 50.5% to 54.1% (p < 0.001). Most (approximately 85.0%) was explained by differential responses of determinants, with unmeasured factors as the highest contributor. Differences in characteristics explained 15% of the increase, with parity and area of residence as the main contributors. The increasing prevalence of maternal complications in Indonesia was mostly due to differential responses of unmeasured factors, which might include increasing awareness of maternal complications and increasing prevalence of underlying causes of maternal complications, i.e., chronic diseases, anemia, and infection. A Further research study which identifies the contribution of these factors to the increasing prevalence of maternal complication is needed.